A new strategy for constructing a dispiro-based dopant-free hole-transporting material: spatial configuration of spiro-bifluorene changes from a perpendicular to parallel arrangement. Issue 24 (25th May 2021) - Wan, Zhongquan; Yang, Jinyu; Xia, Jianxing; Shu, Hongyu; Yao, Xiaojun; Luo, Junsheng; Jia, Chunyang
Abstract : A dispiro-based HTM with a parallel arrangement of two fluorenes was designed by replacing the central carbon atom of Spiro-OMeTAD with cyclohexane. The PCE of a PSC based on dopant-free WH-1 is 19.57%, rivaling that of doped Spiro-OMeTAD (20.29%). Abstract : Due to the low intrinsic hole mobility caused by the orthogonal conformation of two fluorene units in Spiro-OMeTAD which is a classic hole-transporting material (HTM) in perovskite solar cells (PSCs), Spiro-OMeTAD based PSCs generally can only obtain high performances through a sophisticated doping process with dopants/additives, which adds to the cost and complicacy of device fabrication, and also adversely affects the stability of PSC devices. Herein, a novel dispiro-based HTM, WH-1, is designed by cleverly replacing the central carbon atom of Spiro-OMeTAD with cyclohexane, and the spatial configuration of the HTM is changed from vertical orthogonality of the two fluorene units to a parallel arrangement, which is beneficial for the formation of a homogeneous and compact HTM film on the surface of the perovskite film, improvement of intermolecular electronic coupling and intrinsic hole mobility. WH-1 is obtained by two-step facile synthesis with a high yield from commercially available materials. WH-1 is used in PSCs as a dopant-free HTM, which is the first time that the dispiro-based molecule has been applied as a dopant-free HTM, and a power conversion efficiency (PCE) of 19.57% is obtained, rivaling Li-TFSI/ t -BP doped Spiro-OMeTAD in PCE (20.29%), and showing obvious superior long-term stability.